PARIWISATA DAN EKSISTENSI PENDIDIKAN AGAMA DALAM BINGKAI BUDAYA PULAU DEWATA (Analisis Dampak Sektor Pariwisata terhadap Pendidikan Agama Masyarakat Denpasar Bali) - Ketut Wardhana; Amir Fadhilah (Sosio-Didaktika: Social Science Education Journal, 2014)
The development of tourism in Bali has caused structural changes from agrarian economy into a service economy. The positive impact of the tourism sector, among others, increasing the living standards of the people, especially those in the field that has to do with tourism. Infrastructure development in various regions of Bali is directed to facilitate transportation and communication between regions. While the negative impact that arises is the commercialization, commodification, and profanation, the traditions and customs remain well-preserved through the implementation of a religious ritual (yajna) in everyday life. This condition is a process of dynamic equilibrium, ie the awareness of the people of Bali to constantly adapt and tolerate what happens outside, but on the other hand they aware that they are to keep their tradition.